Food politics, and controversial technologies - Walters, Reece (Criminological connections, directions, horizons, 2025)
There is no doubting Nigel South's substantial influence on sociological and criminological thinking. He has immensely advanced discourses about drugs, health, and harm reduction policy; he pioneered scholastic pathways in green criminology and environmental crime; and he has been a beacon of inspirational innovation for cutting-edge ideation that connects socio-legal disciplines for global social justice. This chapter captures his contributions and seeks to demonstrate the importance of his works that intersect socio-legal critiques of power and politics to examine food security and environmental harm. This chapter explores the ways that criminology continues to engage with global food security and asserts the importance of ‘knowledge politics’ in critiquing the role of technology in future food production.